Child Development and Emergent Literacy - Whitehurst, Graver J.; Lonigan, Christopher J. (Child development, 1998)
Emergent literacy consists of the skills, knowledge, and attitudes that are developmental precursors to reading and writing. This article offers a preliminary typology of children's emergent literacy skills, a review of the evidence that relates emergent literacy to reading, and a review of the evidence for linkage between children's emergent literacy environments and the development of emergent literacy skills. We propose that emergent literacy consists of at least two distinct domains: inside-out skills (e. g., phonological awareness, letter knowledge) and outside-in skills (e. g., language, conceptual knowledge). These different domains are not the product of the same experiences and appear to be influential at different points in time during reading acquisition. Whereas outside-in skills are associated with those aspects of children's literacy environments typically measured, little is known about the origins of inside-out skills. Evidence from interventions to enhance emergent literacy suggests that relatively intensive and multifaceted interventions are needed to improve reading achievement maximally. A number of successful preschool interventions for outside-in skills exist, and computer-based tasks designed to teach children inside-out skills seem promising. Future research directions include more sophisticated multidimensional examination of emergent literacy skills and environments, better integration with reading research, and longer-term evaluation of preschool interventions. Policy implications for emergent literacy intervention and reading education are discussed.